Stereoselective Synthesis of 1-Fluoro-exo,exo-2,6-diaryl-3,7-dioxabicyclo[3.3.0]octanes: Synthesis of (±)-1-Fluoromembrine - Teerachai Punirun (2018)
© 2015 American Chemical Society. Stereoselective synthesis of 1-fluoro-exo,exo-2,6-diaryl-3,7-dioxabicyclo[3.3.0]octanes is described. The synthetic strategy involves stereoselective fluorination of 3,4-trans-4,5-cis-3-aroyl-5-arylparaconic esters using Selectfluor to afford the corresponding fluorinated paraconic esters in good yields as a single isomer, which are subjected to reduction employing LiAlH4or DIBALH followed by furofuran formation under acidic or Lewis acid conditions to afford a series of 1-fluoro-exo,exo-furofurans in moderate yields. The synthetic protocol also provides an access to (±)-1-fluoromembrine.